Diversity and inclusion for rodents: how animal ethics committees can help improve translation - Piotrowska, Monika (Journal of medical ethics, 2025)
Translation failure occurs when a treatment shown to be safe and effective in one type of population does not produce the same result in another. We are currently in a crisis involving the translatability of preclinical studies to human populations. Animal trials are no better than a coin toss at predicting the safety and efficacy of drugs in human trials, and the high failure rate of drugs entering human trials suggests that most of the suffering of laboratory animals is futile, creating no commensurate benefit for human patients. Here, I argue that animal ethics committees have a role to play in getting us out of this crisis. Inadequate representation is a known contributor to translation failures and is a matter of both scientific and ethical concern. Ethical review committees have the authority to address it by reprioritising the values already enshrined in their guiding principles.